Legal Protection of the Bensu in Trademark from an Intellectual Property Perspective (Case Study of Central Jakarta District Court Decision 57/Pdt.Sus-Hki/Mark 2019/Pn Niaga Jkt.Pst) - Rahmayani, Rahmayani; Sendy, Beby (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
Trademark disputes reflect one of the intellectual property law conflicts that have attracted widespread attention in Indonesia. One of them is the Bensu trademark dispute involving Ruben Samuel Onsu, a public figure and PT Ayam Geprek Bensu Sujono, a business entity that claims exclusive rights to use the name "Bensu". The dispute is in the spotlight because it not only concerns the formal legal aspects related to trademark registration, but also considers the concept of first use and good faith in conducting business. In addition, the complexity of this case provides an overview of how trademark disputes can affect legal protection for business actors, especially in the highly competitive food and beverage industry. As one of the important cases in the Commercial Court, this case provides an important decision for the application of trademark law principles in Indonesia and becomes the basis for evaluating intellectual property rights protection in the future